2021
DOI: 10.1002/suco.202100230
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and prediction of copper slag incorporated self‐compacting concrete using artificial neural network

Abstract: This research work is aimed to carryout experimental investigation on copper slag incorporated self-compacting (SCC) concrete; here, copper slag is used as a replacement to fine aggregate in the range of 0-100%. The self-compacting concrete is manufactured with powder matrix incorporating cement, flyash, metakaolin, and silicafume. The powder matrix is decided based on the objective of flow properties and strength properties. The fresh concrete properties of various mixes were studied and collected. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Most studies showed that in addition to the concentration of chloride ions, increasing the temperature also significantly reduces the chloride ions penetration resistance. [30][31][32] The use of artificial intelligence in the field of civil engineering [33][34][35][36][37][38][39][40][41][42][43][44] today more than ever is being considered. 45 The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies showed that in addition to the concentration of chloride ions, increasing the temperature also significantly reduces the chloride ions penetration resistance. [30][31][32] The use of artificial intelligence in the field of civil engineering [33][34][35][36][37][38][39][40][41][42][43][44] today more than ever is being considered. 45 The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The use of artificial intelligence in the field of civil engineering 33–44 today more than ever is being considered 45 . The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple experiments are performed to identify the fresh properties of SCC. 74,75 The most commonly used fresh state tests in SCC are slump flow and V-funnel tests. During this study, it was observed that V-funnel and slump flow experiments were applied in 90-95% of the studies related to SCC in the literature.…”
Section: Methods and Model Developmentmentioning
confidence: 99%
“…Additionally, fresh and mechanical properties were also included in the inputs of ANN alongside the composition of the SCC in order to predict the amount of required WMP. Multiple experiments are performed to identify the fresh properties of SCC 74,75 . The most commonly used fresh state tests in SCC are slump flow and V‐funnel tests.…”
Section: Methods and Model Developmentmentioning
confidence: 99%
“…According to the thermal conductivity of the components used in concrete at elevated temperatures, deterioration and fragmentation occur. In order to overcome this situation with minimum damage, concrete mixtures with high strength and durability and low degree of exposure to heat should be developed [2,20].…”
Section: Prior Artmentioning
confidence: 99%